Atlas of Dermatology in Internal Medicine - Sánchez, Néstor P. (Springer New York : Imprint: Springer, 2012)
Atlas of Dermatology in Internal Medicine is the only concise text-atlas to cover the most common and most important cutaneous manifestations of systemic disease in children and adults.  It features more than 150 clinical photographs that are accompanied by format-driven, clinically focused text on the diagnosis and management of cutaneous manifestations of connective tissue, pulmonary, renal, GI, endocrine, malignant, infectious, and HIV disease.  There is also a separate chapter on skin diseases commonly seen in the ICU.  A special feature is its systematic coverage of clinically relevant dermatopathology. The book is a helpful tool for physicians and trainees in internal medicine, family medicine, pediatrics, emergency medicine, and critical care medicine, as well as family, emergency, and critical care nurse practitioners.